A Buyer-Based Measure of Seller Concentration - Iwan Bos (Mathematics, 2022)
In most markets, buyers differ in their ability or willingness to switch supplier. This note proposes a novel industry concentration measure that takes this heterogeneity into account. The index increases in the share of captive sales, coincides with the Hirschman–Herfindahl Index when none of the buyers are captive, and takes the “pure monopoly” value of 1 when all are captive.